Pengaruh Motivasi Kerja dan Disiplin Kerja terhadap Kinerja Pegawai pada Kantor Kelurahan Harapan Jaya - Monica Sasqia Anwar; Supriyanto Supriyanto (Journal on Education, 2023)
For organizations that can provide services, including such governm:ent agencies focused on providing community service, accessibility and services are essential. Employees at the Harapan Jaya Village Office functioned as the study's subject in this quantitative research. methods for collecting information using questionnaires. The study's results suggested that the variables "Work Motivation" and "Work Discipline" A measured f value of 70.566 with a probability value of 0.000 and a table f value of 3.20 were obtained from the results of the simultaneous calibration in the f test. The ftable's estimated value is 70.566 > 3.20, and its significance level is 0.05 is 0.000. As a result, H1 is accepted, revealing that motivation (X1) and discipline (X2) have a significant impact on work perfomance (Y).